PERAN REGULASI DALAM MENGATUR PERDAGANGAN ONLINE DI INDONESIA: KEPATUHAN, PENYELESAIAN SENGKETA, DAN DAMPAKNYA PADA BISNIS ONLINE - Putra, Dwi Savedo Yusuf Ardiyanto (HUKMY : Jurnal Hukum, 2023)
Abstract. The role of regulation in governing online trade in Indonesia is of paramount importance. Regulations such as the Electronic Trading Law No. 19 of 2016 (UU ITE), the Consumer Protection Law, and other regulations constitute the legal framework overseeing online business practices. These regulations aim to ensure that online trade occurs fairly, safely, and reliably. However, there are still several challenges to contend with in online commerce. One of them is the resolution of disputes, which often proves complex, particularly in the context of cross-jurisdictional disputes. Additionally, compliance with regulations, such as tax regulations and consumer protection, becomes a critical issue. Some online business actors may not adhere to these rules. The conclusion drawn from this research is that compliance with regulations is the key to preserving the integrity of online businesses, protecting consumers, and preventing legal risks. Furthermore, more efficient dispute resolution mechanisms and stronger Online Dispute Resolution (ODR) mechanisms are required to address disputes in online trade. Recommendations that can be made include the updating and strengthening of regulations that are responsive to technological changes and consumer behaviors. Additionally, a more active approach to law enforcement and oversight of online business actors should be implemented. This way, we can create a fair, safe, and trustworthy online trading environment in Indonesia.